Crowdsourcing for 3D cultural heritage for George Town UNESCO World Heritage Site - Ch'ng, Eugene (2018)
The uniqueness of George Town as a complex living web of social, cultural and economic activities embedded within built environments presents a challenge for 3D digital documentation, and this even for organisations with large financial resources. This challenge presents a barrier when digital cultural products are needed to enhance site documentation and conservation, facilitate accessibility for academic studies and research, and fuel the creative economy, and many more benefits which usually accompany digitalisation activities globally. Whilst digital transformation may appear daunting, present technologies are sufficiently developed for quick adoption and use by both individuals and small organisations. This paper gave argument to the use of 3D technologies in combination with crowdsourcing mechanisms suited for the World Heritage Site and the benefits that should follow if George Town’s cultural heritage is digitised and subsequently digitalised.